The gesture imitation test in dementia with Lewy bodies and Alzheimer's disease dementia - Li, Xudong; Shen, Miaoxin; Han, Ziling; Jiao, Jinsong; Tong, Xiaopeng (Frontiers in Neurology, 2022)
Objectives Dementia with Lewy bodies (DLB) is the second most common type of neurodegenerative dementia following Alzheimer's disease dementia (ADD). This study investigated the diagnostic role of the gesture imitation test in detecting DLB and differentiating DLB from ADD. Methods A total of 63 patients with DLB, 93 patients with ADD, and 88 healthy controls were included in this study. All participants were administered the gesture imitation test, the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the clock drawing test (CDT), and other neuropsychological tests. Results The patients with DLB performed worse than the healthy controls in the global scores and on every item of the gesture imitation test (p < 0.001). The area under the curve (AUC) for the global scores was 0.889 (p < 0.001) in differentiating the DLB and control groups. Item 4 was a better discriminator, with a sensitivity of 79.37% and a specificity of 79.55%. The AUC for the global scores decreased to 0.593 and the difference was marginal (p = 0.079) in differentiating the DLB and ADD groups. The patients with DLB performed worse on Items 1 and 4 compared with the patients with ADD (p = 0.040, 0.004). The gesture imitation test was positively correlated with the scores of the MMSE (r = 0.355, p = 0.017), the MoCA (r = 0.382, p = 0.010), and the CDT (r = 0.407, p = 0.005) in patients with DLB. Conclusion The gesture imitation test is an easy, rapid tool for detecting DLB and has a role in differentiating DLB from ADD, especially in Items 1 and 4.